THE INFLUENCE OF UNDERWRITER REPUTATION, FIRM SIZE, FIRM AGE, AND LEVERAGE ON IPO STOCK UNDERPRICING ON THE INDONESIA STOCK EXCHANGE DURING 2020–2024 - Ni Putu Mimi Wahyuni; Ni Ketut Rasmini (RADJA PUBLIKA, 2026)
The rapid growth of Indonesia's economy and business environment has encouraged companies to seek external financing to sustain and expand their operations through equity issuance in an Initial Public Offering (IPO). Drawing on Signaling Theory, firm characteristics and IPO supporting parties are regarded as quality signals that may influence investors' decisions and potentially lead to stock underpricing. This study aims to examine the effects of underwriter reputation, firm size, firm age, and leverage on the level of IPO underpricing among companies listed on the Indonesia Stock Exchange (IDX). The study population comprised 267 companies that conducted IPOs on the IDX, of which 184 companies were selected as the research sample based on predetermined sampling criteria. A total of 920 observations were analyzed, representing the selected firms over the five-year study period from 2020 to 2024. This study employed a quantitative research approach, and the data were analyzed using multiple linear regression with SPSS software. The findings reveal that underwriter reputation and firm age have a negative effect on IPO underpricing, whereas firm size has a positive effect. In addition, leverage is found to have a negative effect on IPO underpricing. These findings suggest that reputable underwriters, more established firms, and higher leverage levels reduce IPO underpricing by providing positive signals regarding firm quality and financial discipline. Conversely, larger firms tend to experience higher levels of underpricing because of stronger investor expectations and more optimistic market responses toward newly issued shares. Overall, the findings highlight the importance of both firm-specific characteristics and underwriter reputation in determining the level of IPO underpricing Keywords: IPO underpricing, underwriter reputation, firm size, firm age, leverage, Initial Public Offering (IPO).